2011
DOI: 10.1111/j.1559-1816.2011.00767.x
|View full text |Cite
|
Sign up to set email alerts
|

How Do Happy Leaders Enhance Team Success? The Mediating Roles of Transformational Leadership, Group Affective Tone, and Team Processes1

Abstract: Extending previous research regarding the relationship between leader positive moods and team performance, the present study examined 2 mediating mechanisms that explain the leader positive moods-team performance linkage: transformational leadership, and positive group affective tone. Data were collected from 85 sales teams (85 team leaders, 365 team members). Structural equation modeling analyses were performed to test the hypotheses. The results showed that leader positive moods not only directly enhanced te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(143 citation statements)
references
References 92 publications
(196 reference statements)
6
132
3
2
Order By: Relevance
“…For instance, George and Bettenhausen [55] found that leader positive mood was positively related to work group sales performance. Likewise, Chi and colleagues [7] found that leaders' positive mood was positively associated with sales teams' performance. Particularly in settings such as the present study, where I framed the task as fun and where it was conducted in an enjoyable setting, positive mood has been shown to be beneficial [45,56].…”
Section: Leaders' Mood and Team Outcomesmentioning
confidence: 96%
See 3 more Smart Citations
“…For instance, George and Bettenhausen [55] found that leader positive mood was positively related to work group sales performance. Likewise, Chi and colleagues [7] found that leaders' positive mood was positively associated with sales teams' performance. Particularly in settings such as the present study, where I framed the task as fun and where it was conducted in an enjoyable setting, positive mood has been shown to be beneficial [45,56].…”
Section: Leaders' Mood and Team Outcomesmentioning
confidence: 96%
“…Group affective tone is different from team members' individual mood because it focuses on consistent reactions within a group and is a homogeneous feeling state that result from comparison with other team members [9]. In contrast to an earlier field study [7], the present study examines the mediational effect of group affective tone in a laboratory study, with strong control over potential third variables that might interfere with the research questions. Moreover, the present study--in addition to team performance and goal commitment-takes potency into account when examining group affective tone as a mediator.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…We focus on mood, consequent to evidence of its crucial role in work settings (George and Jones, 1996), and conceptualize team negative affective tone as a negative mood state that team members experience or feel while in a team (Chi et al, 2011). When there is significant homogeneity across members in terms of negative affect, negative group affective tone is considered to be a meaningful construct at the team level of analysis (George, 1996).…”
Section: Theoretical Backgroundmentioning
confidence: 99%